Functional Traits Drive Dispersal Interactions Between European Waterfowl and Seeds - Almeida, Bia A.; Lukács, Balázs A.; Lovas-Kiss, Ádám; Reynolds, Chevonne; Green, Andy J. (Frontiers in Plant Science, 2022)
Endozoochory by waterfowl is important for a broad range of angiosperms, most of which lack a fleshy fruit. This dispersal function contributes to the formation and maintenance of plant communities and may allow range shifts for plant species under global change. However, our current understanding of what seed or plant traits are important for this dispersal mechanism, and how they relate to variation in waterbird traits, is extremely limited. We addressed this question using a unique dataset identifying the plant species whose seeds are ingested by 31 different waterfowl species in Europe. We used RLQ and fourth-corner analyses to explore relationships between (1) bird morphological and foraging strategy traits, and (2) plant traits related to seed morphology, environmental preferences, and growth form. We then used Generalized Additive Models to identify relationships between plant/seed traits and the number of waterfowl species that disperse them. Although many waterfowl feed intentionally on seeds, available seed trait data provided little explanation for patterns compared to plant traits such as Ellenberg indicators of habitat preference and life form. Geese were associated with terrestrial plants, ingesting seeds as they graze on land. Diving ducks were associated with strictly aquatic plants, ingesting seeds as they feed at greater depths. Dabbling ducks ingest seeds from plants with high light and temperature requirements, especially shoreline and ruderal species growing in or around the dynamic and shallow microhabitats favored by these birds. Overall, the number of waterfowl vector species (up to 13 per plant species) increases for plants with greater soil moisture requirements and salinity tolerance, reflecting the inclination of most waterfowl species to feed in coastal wetlands. Our findings underline the importance of waterfowl dispersal for plants that are not strictly aquatic, as well as for plants associated with high salinities. Furthermore, our results reveal a soil moisture gradient that drives seed-bird interactions, in line with differences between waterfowl groups in their microhabitat preferences along the land-water continuum. This study provides an important advance in our understanding of the interactions that define plant dispersal in wetlands and their surroundings, and of what plants might be affected by ongoing changes in the distributions of waterfowl species.